Correlates of Adiposity among Latino Preschool Children - Mendoza, Jason A (2012)
BACKGROUND: Childhood obesity is at record high levels in the US and disproportionately affects Latino children. However, studies examining Latino preschool children’s obesity-related risk factors are sparse. This study determined correlates of Latino preschoolers’ (ages 3–5 years) adiposity to inform future obesity interventions and policies. METHODS: Latino preschoolers (n=96) from four Head Start centers in Houston, Texas were recruited. Parents reported acculturation and neighborhood safety. Children’s and parents’ height and weight were measured. Children’s television (TV) viewing was measured by TV diaries and physical activity by accelerometers. Linear regression was used with body mass index (BMI) z-score as the dependent variable and covariates sequentially added and retained in four blocks: (1) child age, gender, parent education and BMI, (2) neighborhood safety and parent and child acculturation, (3) TV viewing, and (4) moderate-to-vigorous physical activity (MVPA). RESULTS: In the final model (n=96), only neighborhood disorder (beta=0.30, p=0.005) and MVPA (beta=−0.21, p=0.049) were significantly associated with BMI z-score. CONCLUSIONS: Among Latino preschoolers, higher neighborhood disorder and lower MVPA were associated with greater children’s BMI z-scores.